2014
DOI: 10.14260/jemds/1785
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis C Virus Among Health Care Workers of a Rural Teaching Hospital in Tamilnadu

Abstract: Hepatitis C is an emerging infection in India whose long term implications will be felt in the decades to come. In the present study the seroprevalence of HCV infection among 85 healthcare workers was determined. Blood samples were collected from healthcare workers which included doctors, nurses, lab technicians and lab attenders and the sera was tested for anti-HCV antibodies using third generation immunoassay kit. In our study the prevalence of HCV was 1.17%. It is imperative that health care workers be sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…CDC reported that the incidence of anti-HCV seroconversion in U.S. after accidental percutaneous exposure from an HCV-positive source is 1.8% and that too occurred only from hollow-bore needles as compared with other sharps. In India it was reported to vary between 1.2%-5.7% [58]. The increasing rate of hepatitis C virus (HCV) infection globally, in the community will be directly proportional to the increased risk of occupational exposure among healthcare workers.…”
Section: Hostmentioning
confidence: 99%
“…CDC reported that the incidence of anti-HCV seroconversion in U.S. after accidental percutaneous exposure from an HCV-positive source is 1.8% and that too occurred only from hollow-bore needles as compared with other sharps. In India it was reported to vary between 1.2%-5.7% [58]. The increasing rate of hepatitis C virus (HCV) infection globally, in the community will be directly proportional to the increased risk of occupational exposure among healthcare workers.…”
Section: Hostmentioning
confidence: 99%